1993
DOI: 10.1007/bf00025038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed phosphorus concentration on the emergence and growth of subterranean clover (Trifolium subterraneum)

Abstract: Subterranean clover seed (Trifolium subterraneum cv. Dalkeith) with phosphorus concentrations of 0.75% (high P seed) and 0.48% (low P seed) and of uniform size (2.0-2.4 mm diameter) was used to measure the effect of seed P concentrations on seedling emergence and growth.Seedling emergence numbers were 35% greater for the high P seed, and this effect was independent of external P supply. High P seed also emerged more quickly than low P seed.Leaf emergence was faster and shoot dry weight was greater for seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The Pi concentrations in soil solutions are usually very low (typically less than 1 μM) because most Pi is heavily bonded with the relatively abundant cations aluminum (Al), calcium (Ca), and iron (Fe) (Raghothama and Karthikeyan 2005). Although fertilizer P application can temporarily increase the Pi concentration in soil solution, it is immobilized almost immediately due to sorption of P by soil (Stevenson and Cole 1999). Soil interference only allows plants to acquire P within a few millimetres of root surfaces, and acquisition is determined by the volume of soil explored by plant roots, which is normally less than 1% and rarely reaches 5% (Barber 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pi concentrations in soil solutions are usually very low (typically less than 1 μM) because most Pi is heavily bonded with the relatively abundant cations aluminum (Al), calcium (Ca), and iron (Fe) (Raghothama and Karthikeyan 2005). Although fertilizer P application can temporarily increase the Pi concentration in soil solution, it is immobilized almost immediately due to sorption of P by soil (Stevenson and Cole 1999). Soil interference only allows plants to acquire P within a few millimetres of root surfaces, and acquisition is determined by the volume of soil explored by plant roots, which is normally less than 1% and rarely reaches 5% (Barber 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Soil interference only allows plants to acquire P within a few millimetres of root surfaces, and acquisition is determined by the volume of soil explored by plant roots, which is normally less than 1% and rarely reaches 5% (Barber 1995). As a result, most fertilizer P, often more than 90%, is not taken up by plants with the remainder being retained by soil in sparingly soluble forms (Stevenson and Cole 1999). Hence there is the need to develop systems to improve use of soil and fertilizer P for crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients allocated to seeds will serve as food reserves within the seeds, powering the metabolic processes essential to the growth and development of the seedling (Bewley and Black 1985). Enhanced P concentration in seeds has been shown to improve germination rate and percentage, growth rate, and competitive ability (Parrish and Bazzaz 1985;Thomson and Bolger 1993;Sills and Nienhuis 1995), increase root growth (Milberg et al 1998), and allow for greater P-uptake capabilities (Shane et al 2008;Groom and Lamont 2010). P storage in seeds has been identified as an important adaptive strategy in Proteaceae, a family prominently growing on P-limited soils.…”
Section: Inflorescence Versus Seed Nutrient Allocationsmentioning
confidence: 99%
“…Furthermore, a seedling's ability to capture P from the soil can also be improved by having a large storage of P within the seed Fertilization treatment effect on percent change (i.e., relative difference from the control) in N and P input from a inflorescences and b seeds (Shane and Lambers 2006;Shane et al 2008;Groom and Lamont 2010). A possible mechanism for this greater P uptake was demonstrated by Thomson and Bolger (1993) using seeds of Trifolium subterranean grown in soils of varying P levels. The authors found that a greater P reserve increased emergence rate, percentage seedling emergence, and rate of leaf emergence.…”
Section: Differences Among Sitesmentioning
confidence: 99%
See 1 more Smart Citation